Arabic Word Learning in Novice L1 English Speakers: Multi-modal Approaches and the Impact of Letter Training in the Target Language Script - Cicerchia, Meredith (2023)
This thesis explores early Arabic word learning by beginner level native English speakers who have no prior exposure to the language. While Arabic is considered a difficult language for English speakers to learn, very few studies focus on Arabic as a Foreign Language (AFL) vocabulary acquisition in beginners, despite vocabulary’s central role in language learning. The present research encompasses two separate word learning studies which employed multi-modal learning tasks in a language lab setting to show that novice adult learners can acquire Arabic vocabulary given minimal exposure to target language input accompanied by images and audio. In the first study, response time and accuracy data were used to explain performance on a word learning task and probe difficulty drivers in the target language word set. Findings suggest the number of letters and syllables a word contains can explain response time while the number of Arabic-only phonemes it contains can have a significant impact on accuracy. The second study provided a subset of participants with an Arabic letter-training session and utilized written word forms in a modified version of the target language script. Results showed a significant advantage for the letter-training group across all measures of learning. Findings support the use of letter training at introductory level and suggest novice learners can make use of the Arabic script to support form-meaning mapping in early vocabulary study. Results complement existing work on multi-modal learning paradigms and are discussed in the context of research for AFL. They may be used to support future study design and inform stimulus selection for vocabulary researchers choosing to work with Arabic, and generally serve to advance our understanding of effective approaches to Teaching Arabic as a Foreign Language (TAFL) to English native speakers.